Question

reduction method 2x-y=13 x+y=-1

298

likes1488 views

Seamus

4.9

40 Answers

To solve the system of equations using the reduction method, you can eliminate one of the variables by adding the two equations together or subtracting one from the other. Let's eliminate y by adding the two equations:
2x - y = 13
x + y = -1
Now, add equation 1 and equation 2:
(2x - y) + (x + y) = 13 + (-1)
Combine like terms:
3x = 12
Now, isolate x by dividing both sides by 3:
x = 12 / 3
x = 4
Now that you have found the value of x, you can substitute it into one of the original equations to solve for y. Let's use equation 2:
x + y = -1
4 + y = -1
Subtract 4 from both sides to solve for y:
y = -1 - 4
y = -5
So, the solution to the system of equations is:
x = 4
y = -5

Frequently asked questions (FAQs)

How many kilometers are equivalent to 25 miles?

+

How many different ways can 4 people be seated in a row of 8 chairs?

+

Math Question: Given that triangle ABC is congruent to triangle DEF under the SSS (Side-Side-Side) rule, if AB = 5cm, BC = 7cm, and AC = 3cm, find the corresponding lengths of triangle DEF.

+

New questions in Mathematics